The outcome of bariatric surgery in patients aged 75 years and older - Hanipah, Zubaidah Nor; Punchai, Suriya; Karas, Linden A.; Szomstein, Samuel; Rosenthal, Rahul J.; Brethauer, Stacy A.; Aminian, Ali; Schauer, Philip R. (Springer, 2018)
Background: Bariatric surgery has been shown to be safe and effective in patients aged 60-75 years; however, outcomes in patients aged 75 or older are undocumented. Methods: Patients aged 75 years and older who underwent bariatric procedures in two academic centers between 2006 and 2015 were studied. Results: A total of 19 patients aged 75 years and above were identified. Eleven (58%) were male, the median age was 76 years old (range 75-81), and the median preoperative body mass index (BMI) was 41.4 kg/m2 (range 35.8-57.5). All of the bariatric procedures were primary procedures and performed laparoscopically: sleeve gastrectomy (SG) (n = 11, 58%), adjustable gastric band (AGB) (n = 4, 21%), Roux-en-Y gastric bypass (RYGB) (n = 2, 11%), banded gastric plication (n = 1, 5%), and gastric plication (n = 1, 5%). The median operative time was 120 min (range 75-240), and the median length of stay was 2 days (range 1-7). Three patients (16%) developed postoperative atrial fibrillation which completely resolved at discharge. At 1 year, the median percentage of total weight loss (%TWL) was 18.4% (range 7.4-22.0). The 1-year %TWL varied among the bariatric procedures performed: SG (21%), RYGB (22%), AGB (7%), and gastric plication (8%). There were no 30-day readmissions, reoperations, or mortalities. Conclusion: Our experience suggests that bariatric surgery in selected patients aged 75 years and older would be safe and effective despite being higher risk. Age alone should not be the limiting factor for selecting patients for bariatric surgery.